2021
DOI: 10.1111/1460-6984.12615
|View full text |Cite
|
Sign up to set email alerts
|

Smart speaker devices can improve speech intelligibility in adults with intellectual disability

Abstract: Background: Successful communication is vital to quality of life. One group commonly facing speech and communication difficulties is individuals with intellectual disability (ID). A novel route to encourage clear speech is offered by mainstream smart speakers (e.g., Amazon Alexa and Google Home). Smart speakers offer four factors important for learning: reward immediacy, spaced practice, autonomy/intrinsic motivation and reduced social barriers. Yet the potential of smart speakers to improve speech intelligibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 38 publications
(72 reference statements)
1
21
0
Order By: Relevance
“…Bespoke devices are often high cost and can go out of date, whereas mainstream devices, on the other hand, are relatively low cost and are continually updated by the giant companies who develop them [15]. For example, For example, mainstream smart speakers provide costeffective inclusive support for speech and communication improvement among individuals with ID [48]. However, there is a big range of different devices under the umbrella term of AT, and sometimes, we do not have mainstream alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…Bespoke devices are often high cost and can go out of date, whereas mainstream devices, on the other hand, are relatively low cost and are continually updated by the giant companies who develop them [15]. For example, For example, mainstream smart speakers provide costeffective inclusive support for speech and communication improvement among individuals with ID [48]. However, there is a big range of different devices under the umbrella term of AT, and sometimes, we do not have mainstream alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study noted racial disparities in the automated speech recognition of VHAs (36). Alternatively, another study involving adults with intellectual disabilities had improvements in speech intelligibility after VHA interactions (37). Additionally, commercially available VHA devices are relatively affordable, but that benefit involves the risk of corporate-infused biases and targeted, personalized marketing opportunities (32), which may pose vulnerabilities for older adults.…”
Section: Personal and Ethical Considerationsmentioning
confidence: 99%
“…Results showed that the participants were able to disclose more during the session with the robot than with the human concealer. Again, Smith et al [74] employed Alexa and Google Home with 21 individuals with intellectual disabilities and let them free to interact with the technology for about 12 weeks to assess intelligibility gains. Meanwhile, a control group of 22 people did not use any conversational technology.…”
Section: Methods Of Data Collection (R17)mentioning
confidence: 99%
“…Improving automatic speech recognition modules would enable more self-ruling conversational agents, which would reduce the human task load. For this reason, future work should pursue improving certain technical drawbacks, especially regarding speech recognition problems, also considering more severe cases of speech impairments [3,27,74,77,81]. As a possible research direction, Smith et al [74] suggested implementing a voice profile option, which allows the speech recognition model to adapt to individual voices.…”
Section: Open Research Questions (R21)mentioning
confidence: 99%